Web-based marketing communication to develop brand image and brand equity of higher educational institutions: a structural equation modelling approach - Momen, Md. Abdul; Sultana, Seyama; Haque, A. K. M. Ahasanul (Emerald Group Publishing Ltd., 2019)
Abstract Purpose – Internet-based marketing communication has been an important element for organizations to build brand image and brand equity. Higher education is not an exception. However, conﬁguring the right mix in the age of social networking sites and various online displays and constantly changing algorithm in search engine optimization have become major challenges today. Hence, the purpose of this study is to conﬁgure integrated online marketing communication for the development of brand image andbrand equity forhighereducationalinstitutions. Design/methodology/approach – The study is quantitative in nature. A responsive group of 370 students was chosen from different educational institutions in Malaysia via stratiﬁed random sampling techniques.Bothexploratoryandconﬁrmatoryfactoranalyseswereusedforinterpretingthedata.Totestthe derivedhypotheses,structuralequationmodellingwasused. Findings – In line with contemporary literature, the study revealed positive relationships between brand imageandbrandequity,betweensearchengineandbrandimageandbetweensocialmediaandbrandimage. Therelationshipbetweenonlinedisplayandbrandimagewasnotfoundsigniﬁcant. Research limitations/implications – Future research can be done considering both online and conventional marketing communications for the same purpose. This approach can also be used for private andpublicinstitutionsseparately,consideringtheirdifferencesinnature. Practical implications – Because history and tradition are no more a single tool to attain and retain the positive image and customer-based brand equity, this study can help higher educational institutions to conﬁgure integrated online communication for their target groups, such as students and industry, in the age oftheinternet. Originality/value – This study generates a comprehensive understanding of the impact of Web-based marketingcommunicationtodevelopbrandimageandbrandequityofhighereducationalinstitutions